Aphaereta minuta Nees 1811 - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Aphaereta minuta (Nees, 1811) Distribution in Iran. Isfahan (Ghahari et al. 2011c as Asobara minuta Khajeh et al. 2014), Tehran (Khajeh et al. 2014). Distribution outside Iran. Widely distributed and frequent to common in the Palaearctic region (Papp 2007a), and almost all of Europe (Fischer 1973a). Austria, Azores, Bulgaria, Canary Islands, Croatia, Czech Republic, Faeroe Islands, Finland, France, Germany, Greenland, Hungary, Iceland, Italy, Juan Fernandez Islands, Moldova, Morocco, Netherlands, Poland, Romania, Slovenia, Sweden, Switzerland and Uzbekistan (Yu et al. 2012), Greece (Papp 2007a as Asobora minuta Yu et al. 2012), Korea (2007b; Yu et al. 2012), Madeira Islands (van Achterberg and Aguiar 2009; Yu et al. 2012), Russia (Lelej 2012; Yu et al. 2012), Serbia (Žikić et al. 2000; Yu et al. 2012), Spain (Docavo et al 1985, Tormos 1987; Yu et al. 2012), United Kingdom (Broad et al. 2012; Yu et al. 2012). Host records. This species is reported as a polyphagous gregarious larval-pupal parasitoid of fly species of different size ranges from small Drosophilidae to large Calliphoridae, whose larvae feed on ephemeral food sources such as decaying plant and animal material (Sychevskaya 1964; Vet and van Alphen 1985; Vet et al. 1993). Recorded as a parasitoid of Lucilia sericata and Calliphora vicina Robineau-Desvoidy, 1830 (Diptera: Calliphoridae) (Evans 1933; Fischer 1973a). In Iran, it has been reared from the pupa of Diptera, ex snails (Khajeh et al. 2014). In Spain, it has also been reported as a parasitoid of Lucilia sericata (Docavo et al. 1985; Tormos 1987). Lelej (2012) reported the following dipteran genera as hosts to this species: Scatophaga (Scatophagidae), Calliphora and Lucilia (Calliphoridae), Bercaea, Parasarcophaga, Pterella and Ravinia (Sarcophagidae), Delia , Pegohylemyia and Peregle (Anthomyiidae), Ceratitis (Tephretidae), Hebecnema (Muscidae), Psila (Psilidae), Orygma (Sepsidae), Phytomyza (Agromyzidae) and Eumerus (Syrphidae). Published as part of Gadallah, Neveen S., Ghahari, Hassan, ...